Alpha - Vincent, Rachel (Vincent, Rachel. Shifters., 2010)
The unscrupulous new Council chair has charged Jace, Marc, and me with trespassing, kidnapping, murder, and treason. Yeah, we have been busy. But now it is time to take justice into our own hands. We must avenge my brothers death and carve out the rot at the heart of the Council. It is not going to be easy, and loss seems unavoidable, but I have promised to protect my Pride, no matter what. With a target on my back and Marc at my side, I am heading for a final showdown that can - that will - change everything forever.